(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
Hydrophobic interactions between nonpolar groups of protein molecules play a major role in the formation of the protein framework. These interactions contribute to the folding of protein chains and the formation of a structure. Oxidation-reduction reactions also play a significant role in creating the structural framework of the dough. During mixing of the dough in an air atmosphere, sulfhydryl groups are oxidized by oxygen, which leads to the formation of disulfide bonds. This process strengthens the protein structure, increases its elasticity and strength. Dough is a complex system with various rheological properties, which can manifest as properties of an elastic body and a viscous liquid, depending on the conditions. These properties include viscosity, elasticity, elasticity, plasticity, relaxation and depend on such factors as the amount of deformation and its nature, flour strength, dough moisture, dough processing temperature, formulation and properties of the starting materials. Changing the pH of the environment also affects the structural interactions in the dough. A decrease in the pH level leads to a decrease in structural interaction forces, while an increase in the pH level can lead to an increase in these forces. Experimental studies have shown that the use of gelatin and agar significantly affects the buffering properties of flour. During the first stage of acid titration, it was noticed that the character of the curved water-flour suspensions differs in the stage of initial titration in the pH range up to 5 after the addition of gelatin and agar. These data testify in favor of a possible change in the surface charge of protein molecules. Addition of gelatin (0.5% to flour) changes the buffer capacity of suspensions. The decrease in the pH value after the addition of gelatin indicates that the test sample is the most capable of binding H+ ions, so the decrease in the pH of the system occurs more slowly. For example, the rate of decrease in pH when adding 4 ml of acid during titration is: for rice flour - 0.319 units/ml (control sample), 0.108 units/ml (with the addition of gelatin without flour), 0.312 units/ml (with the addition gelatin and flour); 0.254 (with the addition of agar without flour), 0.306 (with the addition of agar and flour).